Impact of the cardio-hepatic syndrome on outcomes after transcatheter mitral valve edge-to-edge repair. (14th October 2021) - Stolz, L; Orban, M; Karam, N; Lubos, E; Wild, M; Praz, F; Braun, D; Doldi, P; Tence, N; Hagl, C; Mayerle, J; Naebauer, M; et al.
Abstract: Background: The prognostic value of impaired liver function in the presence of moderate-to-severe and severe mitral regurgitation (MR), also called cardio-hepatic syndrome (CHS), for outcomes in patients undergoing transcatheter edge-to-edge repair (TEER) has not been studied yet. Purpose: In this work, we aimed at identifying the prognostic impact of the CHS on two-year all-cause mortality in patients undergoing TEER compared to established risk factors. Furthermore, we evaluated the change in hepatic function after TEER. Methods: Hepatic function was assessed by laboratory parameters of liver function (bilirubin, gamma glutamyl transferase [GGT], alkaline phosphatase [AP], aspartate and alanine aminotransferase [AST and ALT]). We defined CHS as elevation of at least two out of three laboratory parameters of hepatic cholestasis (bilirubin, GGT, AP). The impact of CHS on two-year mortality was evaluated using a proportional hazards Cox model. The change in hepatic function after TEER was evaluated by repeat laboratory testing at follow-up. Results: We included 1083 patients who underwent TEER for highly symptomatic primary or secondary MR at four high volume academic European centers between 2008 and 2019. In 66.4% of patients, we observed elevated levels of either bilirubin, GGT or AP. CHS was present in 23% of patients and showed strong association with a reduced two-year survival (52.9% vs. 87.0% in patients without CHS, p<0.01). In a multivariate Cox regression model, CHS was identified as a strong and independent predictor of increased two-year mortality (hazard ratio 1.49, p=0.03). In patients with successful MR reduction ≤2+ (90.7% of patients), parameters of hepatic function significantly improved from baseline to follow-up (−0.2 mg/dl for bilirubin; −21 U/l for GGT, respectively, p<0.01), while they did not in case of residual postprocedural MR >2+. Conclusions: CHS can be observed in up to 25% of patients undergoing TEER and is associated with impaired two-year survival rates. Successful TEER is associated with decreased levels of hepatic enzymes at follow-up evaluation. Funding Acknowledgement: Type of funding sources: None.